Literatur Review: Pengaruh Implementasi ERP terhadap Kualitas Laporan Keuangan dan Informasi Akuntansi di Era Digital - Juli Teratai Nainggolan; Elisabet Tambunan; Rasentri Mey Sinaga; David Efendi (Jurnal Ilmu Ekonomi dan Bisnis, 2025)
This literature review examines the impact of Enterprise Resource Planning (ERP) on financial reporting quality and accounting management across various organizations. An analysis of 20 journals published between 2019 and 2025 indicates that ERP generally enhances accuracy, efficiency, and transparency in financial reporting, supports accounting process automation, and strengthens internal controls. The effectiveness of ERP depends on system type (SAP, Oracle, Odoo, Cloud ERP), module integration, human resource readiness, and organizational context. Some studies show that ERP does not always improve reporting timeliness or significantly reduce earnings management. Overall, ERP is an effective tool for improving financial information quality and operational efficiency, though successful implementation requires process adaptation, staff training, and proper system integration.